2019
DOI: 10.1093/inthealth/ihz017
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with skilled attendants at birth among married adolescent girls in Nigeria: evidence from the Multiple Indicator Cluster Survey, 2016/2017

Abstract: Background This study examines the factors associated with skilled birth attendants at delivery among married adolescent girls in Nigeria. Methods The study was a secondary data analysis of the fifth round of the Multiple Indicator Cluster Survey conducted between September 2016 and January 2017. Married adolescent girls aged 15–19 y who had live births in the last 2 y preceding the survey were included in the analysis. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…Women within the richest wealth quintile specifically had higher propensity of utilizing maternal healthcare services, compared to their counterparts from the poorest wealth quintile, a finding that is consistent with previous studies in other countries [16,17]. Some studies have specifically found higher likelihood of utilization of ANC services among women in the richest wealth quantile [43,18,10,44], with similar observations on SBA utilization [21,22,27,45]. In Guinea, the main reason for the low likelihood of maternal healthcare utilization among women from poorer households could not be the cost associated with healthcare.…”
Section: Discussionsupporting
confidence: 87%
“…Women within the richest wealth quintile specifically had higher propensity of utilizing maternal healthcare services, compared to their counterparts from the poorest wealth quintile, a finding that is consistent with previous studies in other countries [16,17]. Some studies have specifically found higher likelihood of utilization of ANC services among women in the richest wealth quantile [43,18,10,44], with similar observations on SBA utilization [21,22,27,45]. In Guinea, the main reason for the low likelihood of maternal healthcare utilization among women from poorer households could not be the cost associated with healthcare.…”
Section: Discussionsupporting
confidence: 87%
“…The positive association between higher birth interval and the utilization of unskilled birth attendants may be explained by women having more confidence about receiving assistance from unskilled birth attendants after the first birth and may not seek skilled birth attendants in subsequent pregnancies. Previous studies conducted in Nigeria [69,70] and India [29] have shown that younger women were less likely to use ANC compared to older women, which may explain why those in the youngest age groups (15-24 years) were more likely to utilize unskilled birth attendants in the present study. Also, this study found that women who had frequent ANC (≥4) visits were less likely to be assisted by unskilled birth attendants compared to those who had no ANC visits.…”
Section: Discussionmentioning
confidence: 47%
“…The sub-Saharan African countries included in this study were Ghana, Mali, Burkina Faso, Cote d’Ivoire, Benin, Senegal, Zimbabwe, Gambia, Namibia, Guinea, Nigeria, Gabon, Sierra Leone, Togo, Burundi, Cameroon, Uganda, Ethiopia, Kenya, Comoros, Malawi, Rwanda, Zambia, Angola, Congo DR, Congo, Liberia, Chad, and Lesotho [ 25 ]. The variables of this study were derived with respect to their theoretical relevance, parsimony and practical significance with SBA during delivery [ 20 , 26 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the negative effects of early childbearing on maternal healthcare services utilization [ 14 , 20 , 21 ], it is important to understand how early age at first birth affects the utilization of SBA among young women in SSA, especially because early childbearing could have long term effect on SBA use. Therefore, we estimated the prevalence of early age at first childbirth and skilled birth attendance among young women in sub-Saharan Africa and.…”
Section: Introductionmentioning
confidence: 99%